Borogon: Ethnonym and Ethnic History - Bair Z. Nanzatov; Vladimir V. Tishin (Монголоведение)
Introduction. The article is devoted to the study of the origin and spread of the ethnonym Boroγon (in Russian spelling — Borogon), reflected in the names of administrative territorial units of various taxonomic levels in the territory of Yakutia during the 17th–20th centuries (ulus, nasleg, rod). Goals. The study aims at examining the etymology of the term Boroγon, the territorial area where it was spread and the ways of its spread. Materials and methods. The data included in the paper based on the information from Russian-language documents of the 17th–18th centuries, summarized in the works of B.O. Dolgikh, S.A. Tokarev etc. Those sources, however, provide only fragmentary information about the bearers of Borogon identity. It is also proposed the etymology, supported by linguistic data presented in different lexical and etymological dictionaries and recent results of researches on the development of historical phonetics of the Mongolic and Turkic languages. Results. The phases of allocation of bearers of Borogon identity on the territory of Yakutia in the historical foreseeable period were traced in the paper and, consequently, the spread of area of existence of the name Borogon in different levels of identity that reflected in its use in the naming of administrative territorial units of various taxonomic levels (ulus, nasleg, rod). A hypothesis about the interpretation of the name in its original meaning in connection with the Written Mongolian word boruγa(n) ‘rain’, or, mostly, from the form *boroγan, *boraγan id has been argued. Conditions for the appearance of the ethnic name are discussed from a typological perspective, taking into account the lack of direct parallels among the tribal nomenclature of Mongolic and Turkic peoples. Conclusions. A specific historical example presented by a community bearing the name Borogon demonstrates close contacts between the Turkic and Mongolic populations in the territory of Siberia, and specifically within the Lena-Aldan region. It is assumed that the name Borogon among the Yakut population goes back to a word from the Mongolic environment, probably in the original form *boroγan, *boraγan with the literal meaning ‘rain’. Such version does not encounter obstacles from the point of view of the phonetical laws. At the same time, it is impossible to claim whether for some reason this was the accepted name of a historical group with an awareness of such meaning of the word, or whether the name goes back to the personal name of some authority person reflected in folklore as an eponym. According to formal phonetic characteristics, the form reflected in the Yakut pronunciation demonstrates the characteristics of the languages of the Middle Mongolic period. An indirect historical data indicates the time before the beginning of the 17th century as an upper chronological milestone of the appearance of the name. The example considered in the article once again demonstrates the fact of the participation of the Mongol-speaking population in the ethnogenesis of the Sakha (Yakuts).